2015
DOI: 10.1016/j.jpurol.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of catheterizable continent urinary channels: What do you use, where you put it, and does it matter?

Abstract: Runninghead: Long-term outcomes of catheterizable urinary channels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 28 publications
7
37
0
Order By: Relevance
“…Specifically, we found the problems related to obesity to be significantly more common in patients managed with a Monti–Yang tube (87%; 13/15) or APV (55%; 18/33) compared with patients with a tapered ileum and reinforced ileal–cecal valve (27%; 8/30), P < 0.00015 and P < 0.025, respectively (Table ). We hypothesize that improved blood flow of the tapered ileum might prevent ischemic stricture formation, and that the straight channel of the tapered ileum does not result in the angulation and saculation defects that can arise with weight gain found in patients with an APV or Monti–Yang tube . Our findings regarding significantly more complications found with Monti–Yang tubes compared with an APV are consistent with previously published data .…”
Section: Non‐lethal Complications After Bladder Augmentationsupporting
confidence: 91%
See 2 more Smart Citations
“…Specifically, we found the problems related to obesity to be significantly more common in patients managed with a Monti–Yang tube (87%; 13/15) or APV (55%; 18/33) compared with patients with a tapered ileum and reinforced ileal–cecal valve (27%; 8/30), P < 0.00015 and P < 0.025, respectively (Table ). We hypothesize that improved blood flow of the tapered ileum might prevent ischemic stricture formation, and that the straight channel of the tapered ileum does not result in the angulation and saculation defects that can arise with weight gain found in patients with an APV or Monti–Yang tube . Our findings regarding significantly more complications found with Monti–Yang tubes compared with an APV are consistent with previously published data .…”
Section: Non‐lethal Complications After Bladder Augmentationsupporting
confidence: 91%
“…Similarly, the development of obesity in our patient population is associated with a high incidence of subfascial stricture formation with or without the parallel development of a false passage. We hypothesize that the association of these complications in relationship to obesity is due to vascular compromise of the catheterizable limb that might occur with elongation and angulation of the catheterizable limb that occurs with weight gain . Specifically, we found the problems related to obesity to be significantly more common in patients managed with a Monti–Yang tube (87%; 13/15) or APV (55%; 18/33) compared with patients with a tapered ileum and reinforced ileal–cecal valve (27%; 8/30), P < 0.00015 and P < 0.025, respectively (Table ).…”
Section: Non‐lethal Complications After Bladder Augmentationmentioning
confidence: 82%
See 1 more Smart Citation
“…Two of the largest pediatric series note revision rates of 11.7% and 24%. 5,14 Among 144 adults, Wiesner et al reported 17% revision rate for stomal stenosis; the mean time to stenosis was 43.8 months. 6 Redshaw et al in a study of 61 adult patients with cutaneous catheterizable ileal cecocystoplasty found only 3-13% stenosis rate with a relatively short follow-Surgical revision of catheterizable channel obstruction up of 16 months.…”
Section: Discussionmentioning
confidence: 99%
“…While stomal stenosis, stomal revision procedures and channel continence were similar between APV and Monti channels, patients who underwent Monti catheterizable channels were twice as likely to require subfascial revision at 10 years follow-up. The longer spiral Mmonti channels to the umbilicus carried the greatest requirement for subfascial revision (82,83). Complications continued to arise over the lifetime of the channel.…”
Section: Catheterizable Channelsmentioning
confidence: 99%